Systemic antiviral consumption in Kazakhstan - Yuliya Semenova; Assiya Kussainova; Laura Kassym; Ainur Aimurziyeva; Daniil Semenov; Larissa Makalkina; Nurgul Aldiyarova; Andrey Avdeyev; Lisa Lim (Scientific Reports)
Abstract There is a lack of studies from low- and middle-income countries on systemic antiviral consumption (SAC). This study aims to fill this gap by providing a comprehensive analysis of nationwide antiviral consumption trends in Kazakhstan over a period of 7 years. The defined daily doses per 1000 inhabitants per day approach was utilized. Time series analyses were applied to analyze historical trends in SAC, evaluate the impact of the coronavirus disease-19 (COVID-19) pandemic, and make future projections until 2030. The total SAC increased over the study period, with an annual growth rate of 10.24%. Overall, the antivirals that exhibited the most substantial increases in consumption after 2020 were anti-herpes, anti-HBV/HCV, and anti-influenza agents. Predictive modeling indicated that future expenditures on antivirals will remain stable in the hospital sector, both in absolute terms and per million population (pmp) rates, but are likely to increase in the community sector, both in absolute terms and pmp rates. The study’s findings have important implications for public health policy and resource allocation.